En busca de las nuevas ideas : mediación de la creatividad desde la perspectiva cognitiva. (2014)
This article resumes the research project Exploring Old Ideas in the Quest for New Ones: Pedagogic Experience as Mediation means for the Development of Creativity, undertaken by the authors in the Master Course on Education at the Pontificia Universidad Javeriana. It proposes that, from the perspective of Creative Cognition, creativity represents an inner capacity of human being, which may be developed within favorable learning environments, demystifying thus the common idea of creativity as an issue of genius or inspiration, and placing instead it in the very core of the debate on education.Mediation of educational experience aiming the development of creativity is herein assumed from the particular viewpoint of the Geneplore Model, which conceives it not as a unique and independent process, but rather as a result of various mental, generative and exploratory processes, which may lay the basis for “insight” and discovery. An invitation is made, encouraging the possibility of thinking about alternative mediations, which may overtake the enormous gap between creativity as the inspiration and final goal of educational projects and politics, and the less appealing reality of its actual development within the school context.